Effect of fulvic acid induction on the physiology, metabolism, and lipid biosynthesis-related gene transcription of Monoraphidium sp. FXY-10. (March 2017) - Che, Raoqiong; Huang, Li; Xu, Jun-Wei; Zhao, Peng; Li, Tao; Ma, Huixian; Yu, Xuya
Graphical abstract: Highlights: FXY-10 accumulated a considerable amount of lipids under FA induction. Lipid and protein contents increased rapidly and carbohydrate content sharply declined. ME, accD and GPAT were significantly correlated with lipid accumulation. ACCase, ME, PEPCase activities were related to lipid accumulation. FA-induced strategy could be developed to produce microalgal lipids efficiently. Abstract: Fulvic acid (FA) triggers lipid accumulation in Monoraphidium sp. FXY-10, which can produce biofuels. Therefore, the metabolism shift and gene expression changes influenced by fulvic acid should be investigated. In this study, lipid and protein contents increased rapidly from 44.6% to 54.3% and from 31.4% to 39.7% under FA treatment, respectively. By contrast, carbohydrate content sharply declined from 49.5% to 32.5%. The correlation between lipid content and gene expression was also analyzed. Results revealed that accD, ME, and GPAT genes were significantly correlated with lipid accumulation. These genes could likely influence lipid accumulation and could be selected as modification candidates. These results demonstrated that FA significantly increased microalgal lipid accumulation by changing the intracellular reactive oxygen species, gene expression, and enzyme activities of acetyl-CoA carboxylase, malic enzyme, and phosphoenolpyruvate carboxylase.